EVALUATION OF HERBICIDE SELECTIVITY IN WHEAT (Triticum aestivum L.) CROP - FLECK, NILSON GILBERTO (1995)
Phenoxy compounds have been utilized as herbicides in wheat crop for almost five decades. Compouds with different modes of action, like bentazon, diclofop, and pendimethalin, have more recent use. The objective of this research was to evaluate wheat tolerante to these herbicides under field and weed-free conditions. It was found that the herbicides affected negatively the wheat cultivar tested, being the hormone like herbicides and their mixtures those that caused the greatest injury. Regarding grain yield, 2,4-D formulations amine and ester were equivalents. Wheat characteristics more affected were: plant height, test weight, and grain yield. Among the hormone type products, MCPA proved to be the most tolerated by wheat crop. For the majority of variables evaluated, diclofop, pendimethalin, and bentazon were the compounds better tolerated by wheat, nevertheless the last reduced its grain yield.